Evaluation of serotypes 5 and 8 capsular polysaccharides in protection against Staphylococcus aureus in murine models of infection. Issue 7 (3rd July 2017) - Cheng, Brian L.; Nielsen, Travis B.; Pantapalangkoor, Paul; Zhao, Fan; Lee, Jean C.; Montgomery, Christopher P.; Luna, Brian; Spellberg, Brad; Daum, Robert S.
ABSTRACT: Staphylococcus aureus is the leading cause of nosocomial and community-acquired infections, including soft tissue and skin infections and bacteremia. However, efforts to develop an effective vaccine against S. aureus infections have not been successful. We evaluated serotypes 5 and 8 capsule polysaccharides (CP) CRM197 conjugates as vaccine candidates in murine models of bacteremia, lethal sepsis, and skin infection. The conjugate vaccines elicited a good antibody response, and active immunization of CP5-CRM or CP8-CRM conjugates protected against staphylococcal bacteremia. In the skin infection model, CP8-CRM but not CP5-CRM protected against dermonecrosis, and CP8-CRM immunization significantly decreased the bacterial burden in the lesion. However, neither CP5-CRM nor CP8-CRM protected against mortality in the lethal sepsis model. The results indicate the capsular vaccines elicit protection against some, but not all, aspects of staphylococcal infection.